Nanoparticle-based approaches in the development of breast cancer vaccines: the immunotherapeutic potential of nanobiotechnology - Sevimli, Elif; Ziksahna, Kaan; Adiyil, Rumeysa; Ihlamur, Murat (SPRINGER, 2026)
This review is aimed at exploring recent advancements in nanoparticle-based vaccine platforms for breast cancer immunotherapy. The primary focus is on how nanocarriers such as liposomes, polymeric nanoparticles, virus-like particles (VLPs), gold and silver nanoparticles, and mesoporous silica can enhance vaccine efficacy by improving antigen delivery, immune response modulation, and tumor-targeting precision. The overarching research question addresses the potential of nanobiotechnology in overcoming the limitations of conventional cancer vaccines. A comprehensive literature survey was conducted using scientific databases including PubMed, Scopus, and Web of Science. Peer-reviewed articles published between 2010 and 2025 were screened for relevance. Nanocarrier systems were evaluated in terms of physicochemical properties, immunostimulatory capacity, delivery efficiency, and preclinical or clinical outcomes. Nanoparticles demonstrated enhanced delivery of tumor-associated antigens and adjuvants, resulting in stronger humoral and cellular immune responses in preclinical models. Liposomes and PLGA-based carriers showed promise in improving antigen stability and uptake by antigen-presenting cells. VLPs induced HER-2-specific immunity, while metallic and mesoporous nanoparticles facilitated targeted delivery and immunogenicity. Combinatorial approaches incorporating nanocarriers and immunostimulants enhanced therapeutic efficacy. Representative quantitative outcomes include 96% tumor cell death in vitro for a liposome-based anti-ErbB-2 strategy and 80% complete response in HER2 + breast cancer-bearing mice when an antigen-clustered AuNP nanovaccine was combined with anti-PD-1 therapy. Nanoparticle-based breast cancer vaccines offer a promising immunotherapeutic strategy, with the potential to improve antigen delivery, overcome immune tolerance, and enable tumor-specific responses. However, consistent translation will depend on platform-specific safety profiling, reproducible manufacturing, and subtype-informed clinical designs that match vaccine mechanism to endpoints. Further in vivo validation and clinical translation are essential for optimizing safety, dosing, and scalability.
Keywords: Nanoparticles; Nanobiotechnology; Breast cancer; Cancer vaccines; Immunotherapy; VIRUS-LIKE PARTICLES; MESOPOROUS SILICA NANOPARTICLES; GOLD NANOPARTICLES; DRUG-DELIVERY; IMMUNE-RESPONSES; ANTIGEN; LIPOSOMES; SIZE; ADJUVANT; PEPTIDE; Chemistry; Science & Technology - Other Topics; Materials Science